The detonation phenomenon - Lee, John H. S., 1938- (Cambridge University Press, 2008)
This book introduces the detonation phenomenon for engineers with a background in thermodynamics and fluid mechanics.
Keywords: Detonation waves.; Detonation waves -- Computer simulation.; Explosives.; elektronické knihy; electronic books